Effect of walking in heat-stressful outdoor environments in an urban setting on cognitive performance indoors - Asano, Yuki; Nakamura, Yusuke; Suzuki-Parker, Asuka; Aiba, Shohei; Kusaka, Hiroyuki (Building and environment, 2022)
Office workers and students in Japan routinely move between air-conditioned indoor environments and heat-stressful outdoor environments in summer. It is possible that a short walk in the outdoor environment affects workers' and students’ cognitive performance. However, it is unclear. This study aimed to investigate the effect of walking in a heat-stressful outdoor environment on indoor cognitive performance. In the experiments, a total of 96 participants took a mathematical addition test in an air-conditioned room before and after walking in an actual outdoor environment. Results of the experiments showed that walking outdoors under heat-stressful conditions (UTCI ≧ 44 °C) for 15 min decreased the cognitive performance (percentage of correct answers to numbers of problems solved) by 3.6% compared with that before walking. An analysis focusing on the sleep duration showed a negative relationship between sleep duration and the decrease in cognitive performance. This tendency became particularly clear among the participants whose sleep duration was less than 5 h. The reduction of cognitive performance was more pronounced in male participants than in female participants. Sleep-deprived men who walk in a heat-stressful outdoor environment are more likely to exhibit poor cognitive performance when they return to an air-conditioned room. Japanese office workers and students, especially men, need to be aware of this as they work and study. •This study revealed the effect of outdoor walking on cognitive performance.•A total of 96 participants took a mathematical addition test.•A combination of heat stress (UTCI ≥44 °C) and walking decreased the performance.•There was a significant relationship between sleep duration and performance.•The reduction of the performance was more pronounced in men than in women.